Project Swaziland (Part 3): periodontal health status of 12 year old school children - Gugushe, T S; Rossouw, L M; de Vries, J (The Journal of the Dental Association of South Africa = Die Tydskrif van die Tandheelkundige Vereniging van Suid-Afrika, 1993)
An investigation on the periodontal disease profile and its treatment implications was conducted on a sample of 12-year-old Swazi schoolchildren of the Kingdom of Swaziland using the CPITN index. Only 1.9 per cent of the pupils in the sample were free of periodontal disease and 64.5 per cent had calculus. There was a significant difference (p < 0.05) in the frequency of calculus accumulation between rural and urban pupils. The mean number of sextants with bleeding and calculus was 4.9 and 2.0 respectively while 98.1 per cent of the pupils required TN1 and 65.4 per cent TN2. It would appear that calculus accumulation occurs at a relatively early age amongst children in Swaziland. Moderately trained dental auxiliaries should constitute the backbone of the primary oral health care service in Swaziland.